O estágio supervisionado como espaço formativo do professor que ensina matemática - Gabbi, Gabriela Fontana (2023)
This research is part of the Group of Studies and Research in Mathematics Education (GEPEMat), with concerns focused on teacher training, linked to the Graduate Program in Education (PPGE) in the line of research Teaching, Knowledge and Professional Development, at the Federal University of Santa Maria (UFSM). When dealing with aspects that involve human development and teacher learning, we base the theoretical assumptions on the Historical-Cultural Theory -THC and Activity Theory - AT. Regarding the training of future teachers, the contributions come from authors who articulate the proposals present in this theoretical line. As a general objective, our intention is to understand the relationship between the supervised internship and the learning of future teachers who teach mathematics in the Early Years. Data production took place in two stages, namely: 1) Interviews with teachers who teach classes in the Daytime Pedagogy course/UFSM; 2) Documental research to analyze the internship reports of graduates of the Pedagogy/UFSM course. As a systematization and analysis of the collected data, the proposal of isolated conceptualized by Caraça (1963) and episodes, developed by Moura (2004) were used. Data analysis allowed the organization into three isolates: 1) The initial movement: first steps; 2) Approaches with reality in the insertion in the context of the school; 3) Mathematics teaching actions in the internship: what the reports reveal. The data produced from the analysis of the internship reports made it possible to show that: the first actions of the academics upon arriving at the supervised internship constitute a mobilizing movement of learning to be a teacher, bringing them closer to the teaching activity by enabling the appropriation of the necessary knowledge so that they can organize their teaching practice; that the internship, as an essential part of the formation of the future teacher, is permeated with elements that allow the transition in an effective way from the passage from academic to professor, making teaching an activity, bringing it closer from knowledge to teaching; and that during the internship, the teaching activity can be transformed, along with the reason for doing it. Finally, we show that the internship is an extremely important process in the training of future teachers, and that, despite its development, described in the reports, revealing weaknesses, with regard to the relationship with mathematical knowledge, the relevance of acquiring knowledge in the disciplines related to this area during the Pedagogy course is highlighted